Multiplicity Results Using Bifurcation Techniques for a Class of Fourth-Order m-Point Boundary Value Problems. (18th May 2009) - Liu, Yansheng; O'Regan, Donal
Abstract : By using bifurcation techniques, this paper investigates the existence of nodal solutions for a class of fourth-orderm -point boundary value problems. Our results improve those in the literature.